Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.2 - Rational Exponents - Exercise Set: 57

Answer

$\dfrac{(y^{3}z)^{1/6}}{y^{-1/2}z^{1/3}}=\dfrac{y}{z^{1/6}}$

Work Step by Step

$\dfrac{(y^{3}z)^{1/6}}{y^{-1/2}z^{1/3}}$ Evaluate the power indicated in the numerator: $\dfrac{(y^{3}z)^{1/6}}{y^{-1/2}z^{1/3}}=\dfrac{y^{1/2}z^{1/6}}{y^{-1/2}z^{1/3}}=...$ Evaluate the division and write the answer without negative exponents: $...=y^{1/2+1/2}z^{1/6-1/3}=yz^{-1/6}=\dfrac{y}{z^{1/6}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.